Late-stage C(sp(2))-H arylation of artemisinic acid and arteannuin B: effect of olefin migration towards synthesis of C-13 arylated artemisinin derivatives - Paul, Sayantan; Ghodake, Balaji M. M.; Bhattacharya, Asish K. K. (Chemistry-An Asian Journal, 2023)
In recent years, C-H bond functionalization has emerged as a pivotal tool for late-stage functionalization of complex natural products for the synthesis of potent biologically active derivatives. Artemisinin and its C-12 functionalized semi-synthetic derivatives are well-known clinically used anti-malarial drugs due to the presence of the essential 1,2,4-trioxane pharmacophore. However, in the wake of parasite developing resistance against artemisinin-based drugs, we conceptualized the synthesis of C-13 functionalized artemisinin derivatives as new antimalarials. In this regard, we envisaged that artemisinic acid could be a suitable precursor for the synthesis of C-13 functionalized artemisinin derivatives. Herein, we report C-13 arylation of artemisinic acid, a sesquiterpene acid and our attempts towards synthesis of C-13 arylated artemisinin derivatives. However, all our efforts resulted in the formation of a novel ring-contracted rearranged product. Additionally, we have extended our developed protocol for C-13 arylation of arteannuin B, a sesquiterpene lactone epoxide considered to be the biogenetic precursor of artemisinic acid. Indeed, the synthesis of C-13 arylated arteannuin B renders our developed protocol to be effective in sesquiterpene lactone as well.
Keywords: Arteannuin B; Artemisinic acid; artemisinin; C-H functionalization; Pd-catalysis